The Influence of Digital Literacy on Student Political Participation: A Case Study of Student Movements in Responding to Public Policy - Yuniarto, Bambang; Abiyah, Dina; Sarah, Siti; Ramadhani, Diva (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2025)
The aim of this research focuses on digital literacy, which has a broad influence on students' political participation and helps create movements for change in response to policies directed at the public. The method used includes a literature review and a qualitative approach. In addition, to strengthen the theoretical basis and arguments, a second method is applied through direct interviews, aiming to build a comprehensive understanding of how digital literacy works and how students participate in responding to public policy. The findings show that there are many opportunities, such as using social media, expressing aspirations, and critically examining various information. However, the digital era also presents challenges that require students to improve their digital literacy, especially in relation to political issues. As the future of the next generation, students are expected to have political activity and criticism of the policy. In addition, it is been brought into the light the role of the digital literacy both in reflection and in deeping the reflections on the responsibility of fitting the course of the digital progression that is being designed by the digital literacy.